Implementation of open science in Lithuania - Dovidonytė, Rasa (Nordic Perspectives on Open Science, 2019)
The number of open science policies being adopted in Europe by universities and research institutions is constantly increasing, however many European countries face difficulties while implementing open science practically. This publication reveals the Lithuanian landscape of open science policies and institutional involvement in open science practices. Prerequisites for sustainable and consistent open science implementation such as open science infrastructure, incentives for researchers, research assessment, and repositories' compliance with EC requirements on a national level are discussed.